2.43 kW narrow linewidth linearly polarized all-fiber amplifier based on mode instability suppression. (21st July 2017) - Su, Rongtao; Tao, Rumao; Wang, Xiaolin; Zhang, Hanwei; Ma, Pengfei; Zhou, Pu; Xu, Xiaojun
Abstract: We demonstrate an experimental study on scaling mode instability (MI) threshold in fiber amplifiers based on fiber coiling. The experimental results show that coiling the active fiber in the cylindrical spiral shape is superior to the coiling in the plane spiral shape. When the polarization maintained Yb-doped fiber (PM YDF: with a core/inner-cladding diameter of 20/400 µ m) is coiled on an aluminous plate with a bend diameter of 9–16 cm, the MI threshold is ~1.55 kW. When such a PM YDF is coiled on an aluminous cylinder with diameter of 9 cm, no MI is observed at the output power of 2.43 kW, which is limited by the available pump power. The spectral width and polarization extinction ratio is 0.255 nm and 18.3 dB, respectively, at 2.43 kW. To the best of our knowledge, this is the highest output power from a linear polarized narrow linewidth all-fiberized amplifier. By using a theoretical model, the potential MI-free scaling capability in such an amplifier is estimated to be 3.5 kW.